Cost estimation and management over the life cycle of metallurgical research projects - Odendaal, M M; Vermaak, F NS; Du Toit, E (Southern African Business Review, 2019)
This study investigates whether all expected costs over the life cycle of metallurgical research projects are included in initial, normal and final cost estimates, and whether these costs are managed throughout a project’s life cycle since there is not enough emphasis on the accurate estimation of costs and their management over the life cycle of metallurgical research projects. The study also determines during which phase of the life cycle of metallurgical research projects’ costs are normally determined, during which phase most of the costs are incurred, and during which phase costs are managed. Project life cycles, techniques of cost estimation and cost management are examined. 10A survey was used to gather information by means of face-to-face and telephonic interviews, as well as an electronic questionnaire. The total population of entities in South Africa that conduct metallurgical research projects is small, numbering only 12 in all. The ten entities that conducted the largest metallurgical research projects in terms of average size were selected for this study. 11The conclusion drawn from the survey was that all costs over the life cycle of metallurgical research projects are not taken into account in the initial cost estimate of a project. Costs are mainly managed during the growth phase of a project and not during the introduction phase, when 80% of the costs are normally committed. The implication of this is that cost estimates for metallurgical research projects may not be accurate and costs are not necessarily managed properly throughout the life cycle of such projects. This may lead to cost overruns of project budgets, project budgets being depleted before the delivery stage and research sections running at a loss.